Comparison of Learning Models to Build an Infrastructure for Performance Measurement of E-Learning Systems - (:unkn) unknown (SPRINGER-VERLAG BERLIN, 2009)
In this paper, Models describing the learning process is compared in terms of six different criteria taking distance based education systems into account. The result of this study will be utilized in establishing learning performance assessment system in Adapazari Vocational School where main education is based on e-learning.
Keywords: Learning Process; E-learning; Learning Performance